SLUŽBA U ČAST SV. BARBARI U HRVATSKOGLAGOLJSKIM BREVIJARIMA. - MIHALJEVIĆ, Milan; VELA, Jozo (Slovo (05836255), 2021)
The Office of St. Barbara is preserved in a small number of the Sanctorale part of Croatian Glagolitic breviaries. Through a comparative analysis of the text in the three breviaries where it has been preserved, this paper provides a presentation of the linguistic features of the Office. There are certain differences in the length of the readings and the arrangement of the readings and the singing parts, but the texts in the breviaries are generally the same. Consequently, there are no significant differences between breviaries at the linguistic level either. In general, it can be said that the First Beram Breviary has more regular (Church Slavonic forms) in the Office than the Vatican breviary Illirico 10 and Bribir breviary. Non-Slavic protographs of texts within the service have not been identified. However, to the extent possible, certain comparisons have been drawn which point out to possible directions for further research. The use of the noun spasь instead of isusь as a feature of the oldest Croatian Glagolitic tradition, as well as the fact that the template of the Martyrdom of St. Barbara was Greek, suggests that the Office came into preserved breviaries by copying from a much older templates.